Monomers for Adhesive Polymers, 14 Synthesis and Radical Polymerization of 4‐[11‐(Acryloyl‐methyl‐amino)‐undecyloxy]‐phthalic Acid and {10‐[1, 3‐Bis(methacrylamido)‐propoxy]‐decyloxy}‐phthalic Acid. Issue 7 (20th January 2014) - Lamparth, Iris; Fischer, Urs K.; Pavlinec, Juraj; Kleinova, Angela; Moszner, Norbert
<x xml:space="preserve">Abstract</x> The polymerizable phthalic acid derivatives 4‐[11‐(acryloyl‐methyl‐amino)‐undecyloxy]‐phthalic acid (1) and {10‐[1, 3‐bis(methacrylamido)‐propoxy]‐decyloxy}‐phthalic acid (2) are synthesized from the MOM‐ester of 4‐hydroxy‐phthalic acid and the corresponding bromo‐alkyl‐(meth)acrylamides. The synthesized monomers are characterized by 1H NMR, 13C NMR, and IR spectroscopy. The acrylamide 1 is insusceptible toward hydrolysis in aqueous media, strongly acidic and highly reactive in free radical polymerization. With these characteristics, 1 fulfills important requirements for the application in water‐based single‐bottle adhesive formulations. A deviation from the standard reaction kinetics is found for the free‐radical homopolymerization of 1 in methanol with AIBN as initiator. The overall activation energy Ea is 66.2 kJ mol−1.<inline-graphic xlink:href="ark:/27927/pghqpm6p7j" content-type="mame201300332-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />